Cover Feature: Efficient and Spatially Controlled Functionalization of SBA‐15 and Initial Results in Asymmetric Rh‐Catalyzed 1, 2‐Additions under Confinement (ChemCatChem 10/2021). Issue 10 (21st April 2021) - Beurer, Ann‐Katrin; Kirchhof, Manuel; Bruckner, Johanna R.; Frey, Wolfgang; Baro, Angelika; Dyballa, Michael; Giesselmann, Frank; Laschat, Sabine; Traa, Yvonne
Abstract : The Cover Feature shows asymmetric catalysis on mesoporous silica, which is selectively functionalized in a spatially controlled manner with highly selective complex catalysts on the mesopore walls. In their Full Paper, A.‐K. Beurer et al. describe a new method, which ensures with a special control step that exclusively the mesopore surface is functionalized with a clickable linker. This makes it possible to study unambiguously confinement effects during catalyzed reactions. First, the silanol groups on the particle surface and in the pore entrances of the SBA15 are passivated. Then, the template is removed by solvent extraction and, afterwards, the pore walls are functionalized with 3‐azidopropyltriethoxysilane before the catalyst is clicked on the pore walls. In initial experiments of asymmetric Rh‐catalyzed 1, 2‐addition, a high enantiomeric excess is obtained.More information can be found in the Full Paper by A.‐K. Beurer et al.